(untitled) (Proceedings of Southern Federal University. Philology, 2019)
Natalia I. Lopina (Rostov-on-Don, Russian Federation) The article presents the experience of designing the structure of the lesson with the inclusion of innovative components; the necessity of reorganization of the survey system as an important link in the diagnosis of acquired competencies is substantiated. The mutual influence and rational combination of various methodological approaches is investigated by approbation in the classroom setting; the characteristic features of the presentation of the material in the format of innovation in the training of first-year students are determined. The considered strategies are invariant for modeling the educational process taking into account current trends. Key words: structure classes, the semantic centre classes, adaptation, online survey, educational games occupation structure, sense-forming center of the lesson, adaptation of first-year students, interactive survey, educational games. DOI 10.23683/1995-0640-2019-3-196-204